Worm-like porous and defect-structured cadmium stannate photoanodes for enhanced solar water oxidation. Issue 4 (1st February 2022) - Peng, Pan; Wang, Ping; Cai, Zhengyang; Zhang, Jiajia; Hu, Yu; Xu, Jingcheng; Wang, Xianying
Abstract : The importance of hybrid microwave annealing technology in ultrafast fabrication of deficient cadmium stannate photoanodes with a worm-like porous structure and significant enhancement of solar water oxidation performance and stability. Abstract : The work aims to elucidate the importance of hybrid microwave annealing technology (HMA) in ultrafast fabrication of deficient cadmium stannate (Cd2 SnO4 ) photoanodes with a worm-like porous structure and significant enhancement of solar water oxidation performance and stability. Comparison of three synthetic routes and experimental characterization revealed that relative to conventional thermal annealing (CTA) or even with extra HMA for 5 min (optimal), direct HMA for only 8 min can form cubic Cd2 SnO4 thin films of unique worm-like and highly porous nanostrucures with a large interfacial surface area, high degree of phase crystallinity and high-concentration defects. The obtained results from the photoluminescence spectra and the charge efficiency measurements collaboratively verified that compared to using CTA treatment solely, the HMA treatment is effective in significantly improving charge separation, recombination and transfer processes, mainly by an over 13.5-fold increase in the bulk charge separation efficiency. Benefiting from these merits, under optimized conditions the HMA treated Cd2 SnO4 film exhibited a remarkable 6-fold and 2-fold solar photocurrent enhancement compared with those of the CTA treated one and the combined CTA-HMA treated one, respectively, and an IPCE of 39% at 300 nm and 18% at 350 nm at 1.7 V versus RHE. Despite a high external bias required in this case, the study provides a simple route for synthesis of ideal Cd2 SnO4 photoanodes which can be further extended to doping engineering and non-noble metal cocatalyst deposition.